Mesclagem conceptual e compressão de relações vitais: a construção de objetos-de-discurso e negociação de sentidos em língua inglesa. - Santana, Joelton Duarte de (2012)
Considering the hypothesis that English language learners at the learning moment negotiate and share collective or individually meaning during the conversation, we intend, in this study, to analyze which are the linguistics and cognitive processes involved in the English meaning construction. According to the Blending Theory (Fauconnier & Turner 1998, 2002) as well as Objects of Discourse Theory (Mondada 1994, 1999, 2002), this work aims at understanding, analyzing and describing the vital relations compressed while meaning are negotiated in English language as well as the structures that rise up at the objects of discourse format through blending and vital relation compression processes. We also intend to know how much blending process, objects of discourse and meaning negotiation through discursive, social and cognitive placed practices could make an English language learner able to build public versions of the world. Considering three classroom classes transcription analyses - undergraduate, graduate and conversation course of language we intend to understand how much the meaning negotiation may become a strategy of English language objects of discourse construction and how they might provide interaction at this target language while provide to these learners linguistics and social cognitive sources of world description. We believe human beings are able to build world version by language usage to interact at the specific social communicative and placed contexts. We believe that the meaning it is not only relationed to linguistic aspects but cognitive aspects as well. So we see the language as capable to create a reality that belongs to its own and is mediated by cognitive activities.